Effect of nutritional intake on anthropometry status of rural pregnant women in Ifelodun local government area, Kwara State (2017)
Rural women contribute significantly to the national economy by their activities in terms of agriculture and food security under normal and special condition such as pregnancy in which the body requires increase nutrient intake. Many rural women farmers have poor health status, which could be due to workload and poor nutrition. This study examined the effects of nutritional intake on the anthropometry1 status of rural pregnant women in Ifelodun local government area, Kwara Slate. Multistage sampling procedure was used to select 130 respondents. Primary data were collected using a well-structured questionnaire, and were analysed using descriptive and inferential statistics. Results showed that majority (68.5%) of the respondents were between age 20-29 years, Muslims (69.2%), with primary school education (43.8%), marketers (76.2%,) with income between 4000- 6000 naira and have at least two (2) children. Results also show that educational background (x2 = 5. 508; p= 0.044), age (r= 0.241; p = 0.006), income (r = 0.358; p = 0.030), nutritional intake (r =0.550; p = 0.030), had significant relationship on their anthropometry status. Also there was a significant weight gain during period of pregnancy (t = 63.861; p = 0.000). It recommends that pregnant women should be empowered economically to have a better source of income that will enable them afford better nutrition for proper development and growth of foetus.